O potrzebie wierności drobiazgom - Wiesław Ratajczak, Wiesław Ratajczak (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
This article concerns the book Prus. Śledztwo biograficzne [Prus. A biographical investigation] by Monika Piątkowska, a new biography of the nineteenth-century writer that enjoys great readership. However, it contains many superficial interpretations and simplifying applications. Piątkowska argues that in his stories and novels, Bolesław Prus included many autobiographical elements. This interpretation key fails. The schematic depiction of the psychological layer of literary works, the lack of references to previous studies of the work and life of Prus, disregarding the intellectual dimension of his biography – these are the most significant drawbacks of this book. The author of the review shows examples of the researcher’s simplifications and lack of competence.